Performance of paprika and paprika alike chillies (Capsicum annuum L.) under warm humid tropics - P A Mathew, K N Shiva, T J Zachariah, N K Leela (Journal of Spices and Aromatic Crops, 2013)
A study was conducted to evaluate the performance of 21 paprika alike chillies (indigenous germplasm) and nine paprika lines (exotic collections) under rain-shelter. Highly significant variation was recorded among the genotypes for all the characters. The results indicated that Kt-Pl-19 variant – I, ICBD-6, ICBD-12, ICBD-13, ICBD-11 were promising for yield and yield attributing characters, while ICBD-12, ICBD-11, ICBD-2, ICBD-13, Kt-Pl-19 variant – I proved to be better for high seed numbers. With respect to total extractable colour, ICBD-5, ICBD-7, ICBD-4, ICBD-1, ICBD-18 were measured with high colour value, among the indigenous germplasm. Among the exotic collections, PBC-171, SSP-1999, EC-18, EC-45, EC-71 proved better for yield and yield attributing characters. The genotypes, Paprika King, EC-45, PBC-171, EC-43 produced maximum number and weight of seeds, whereas PBC-171, IMI-5, EC-71, EC-45 were found promising for high colour value. Based on these observations, the genotypes Kt-Pl-19 variant -I, ICBD-6, ICBD-12, PBC-171, SSP-1999 and EC-18 were found suitable for high yield, whereas ICBD-12, ICBD-11, Paprika King, EC-45 and PBC-171 for high seed numbers and ICBD-5, ICBD-7, ICBD-4, PBC-171, IMI-5, EC-71 for high colour value in Kerala. Among the various traits, wide range of variation was recorded for number of seeds per fruit and narrow range of variation for fruit length.